Evaluation of hypertension screening guidelines implementation at the public health centers in Tabanan District, Bali, Indonesia - Ratnata, Gede Agung; Duarsa, Dyah Pradnyaparamita; Ani, Luh Seri (Public Health and Preventive Medicine Archive, 2021)
Background and purpose:World Health Organization (WHO) reported the number of people with hypertension worldwide reached one billion in 2015. Hypertension screening is an effort to manage and control hypertension through hypertension management stages. This study aims to explore in-depth the implementation of hypertension screening guidelines performed by the public health centers (PHCs). Methods: This is a qualitative exploration with an exploratory case study approach by adopting the Lawrence W. Green Theory. This study was conducted in two PHCs in Tabanan District, those with the highest and the lowest target achievement. The factors examined were the implementation of guidelines and factors affecting it. The data were collected using in-depth interviews with ten informants and data were analyzed using thematic methods. Results: We found the predisposing factors of the implementation including the management of Health Operational Assistance (HOA) funds, the grouping of targets at risk of hypertension, hypertension screening guidelines, and the attitudes and beliefs of the officers and the community. The driving factors consisted of the lack of community participation. The inhibiting factors were indicated by the insufficient number of health workers and community support. Conclusion: There are several obstacles for the implementation of hypertension screening guidelines both from the health services side including budget allocation and community participation. Therefore, more thorough planning and measures to improve participation is needed.